2021
DOI: 10.3390/biom11020285
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cellular Prion Protein in Invasion and Metastasis of Lung Cancer by Inducing Treg Cell Development

Abstract: The cellular prion protein (PrPC) is a cell surface glycoprotein expressed in many cell types that plays an important role in normal cellular processes. However, an increase in PrPC expression has been associated with a variety of human cancers, where it may be involved in resistance to the proliferation and metastasis of cancer cells. PrP-deficient (Prnp0/0) and PrP-overexpressing (Tga20) mice were studied to evaluate the role of PrPC in the invasion and metastasis of cancer. Tga20 mice, with increased PrPC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…The IQSEC2 and its family members are Arf-nucleotide exchange factors and have been implicated in angiogenesis and tumor metastasis ( D'Souza and Casanova, 2016 ). Several other genes among them, including NMNAT1 ( Yaku et al., 2018 ), MAGED2 ( Jia et al., 2019 ), SLC12A7 ( Brown et al., 2018 ), IGFBP7 ( Paulitschke et al., 2019 ), HUWE1 ( Vaughan et al., 2015 ), PLS3 ( Ueo et al., 2015 ), PRNP ( Cha et al., 2021 ), HMGB2 ( Cui et al., 2019 ), LAMP2 ( Damaghi et al., 2015 ), CTSD ( Ketterer et al., 2020 ), etc., have also been linked to the glycolysis, EMT, stemness, and metastasis of the cancer cells. Thus, enhancement of H3K36me3 may preferentially favor the expression of genes contributing to EMT and cancer cell metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…The IQSEC2 and its family members are Arf-nucleotide exchange factors and have been implicated in angiogenesis and tumor metastasis ( D'Souza and Casanova, 2016 ). Several other genes among them, including NMNAT1 ( Yaku et al., 2018 ), MAGED2 ( Jia et al., 2019 ), SLC12A7 ( Brown et al., 2018 ), IGFBP7 ( Paulitschke et al., 2019 ), HUWE1 ( Vaughan et al., 2015 ), PLS3 ( Ueo et al., 2015 ), PRNP ( Cha et al., 2021 ), HMGB2 ( Cui et al., 2019 ), LAMP2 ( Damaghi et al., 2015 ), CTSD ( Ketterer et al., 2020 ), etc., have also been linked to the glycolysis, EMT, stemness, and metastasis of the cancer cells. Thus, enhancement of H3K36me3 may preferentially favor the expression of genes contributing to EMT and cancer cell metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown, by transplanting cell tumors into nude mice, that the lysine-specific histone demethylase 1 (LSD1) demethylates the SEPT6 promoter, thus positively regulating Septin 6 (SEPT6), which, through the TGF-β/Smad pathway, accelerates metastasis in NSCLC [ 62 ]. In addition, it was investigated in in vivo experiments that the overexpression of cellular prion proteins drives the invasion and metastasis of the LC, an effect linked to TGF-β and PD-L1, which is important for the role of regulatory T cells in LC and immunotherapeutic approach [ 63 ]. Furthermore, TGF-β is the major driver of pleural dissemination in metastatic LC; in particular, pleural mesothelial cells that co-cultured with A549 cells expressed high levels of TGF-β and underwent apoptosis and senescence [ 64 ].…”
Section: Tgf-β In Lung Cancer Development and Metastasismentioning
confidence: 99%
“…Regulatory T cells (Tregs), which have immunosuppressive activity ( 50 ), are one of the main targets of cancer immunotherapy ( 51 ). By constructing a lung metastatic model of melanoma in Prnp0/0 and Tga20 mice, it was demonstrated that the increased expression of PrP C induces the development of Tregs by upregulating transforming growth factor-beta (TGF-β) and programmed death ligand-1(PD-L1), thereby promoting tumor progression ( 52 ).…”
Section: Prp C Promotes Cancer Cell Invasion/metastasismentioning
confidence: 99%